Yield stability and association of its component characters in soybean (Glycine max L.) genotypes: YIELD STABILITY IN SOYBEAN - M PALLAVI; G PRAVEEN KUMAR; N SANDHYA KISHORE (Journal of Oilseeds Research, 2019)
The present investigation was carried out to study stability performance for seed yield and its components in 24 soybean varieties using a randomized complete block design. The partitioning of (environment + genotype x environment) mean squares showed that environments (linear) differed significantly for yield and its component characters except for 100-seed weight. Stable genotypes were identified for wider environments and specific environments with high per se performance (over population mean) for seed yield/ha. The investigation revealed that the genotype AMS 243 and DSB 20 possessed desirable stability across the environments. Genotypes AMS MB 5-19, NRC 2007 2-19 were suitable for favourable situations for seed yield.